The Expansion of Tolerance Religion in Dutch Brazil (1624-1654) - Israel, Jonathan (Amsterdamse Gouden Eeuw Reeks, 2007)
This volume about religious tolerance in early modern Brazil comprises two articles. Jonathan Israel, in his contribution, argues that Dutch tolerance in Brazil was unprecedented in the seventeenth century. Catholics and particularly Jews were given freedom of conscience and freedom of private worship in accordance with Dutch guide-lines. Stuart Schwartz, in his article, demonstrates that religious toleration in Dutch Brazil was not exclusively the domain of the Dutch. The Portuguese also widely approved of tolerance at grassroots level, accepting an individual's preference to follow his own path to salvation.